Introducing the professional metamorphosis theory of the BSN students and its application in the nursing education - Dinmohammadi, Mohammadreza; alali, Amir; Peyrovi, Hamid (Advances in Nursing & Midwifery, 2016)
Abstract Background and aim Professional socialization is a critical aspect of nursing students’ development. This process begins with entering into the nursing program and continues after graduation and beginning of professional practice. This paper aimed to introduce the professional metamorphosis theory of BSN students and its application in the nursing education. Materials and methods This study was conducted with the aim of the introduction of the professional metamorphosis theory of BSN students. For this purpose, a search was performed on scientific databases (Pub Med, CINAHL, SID & IranMedex) using the key terms “professional socialization”, “professionalization”, “nursing education”, and “ metamorphosis”. Ultimately 27 scientific articles and 2 Textbooks selected and reviewed. The results were compared with the present theory. Findings In this study, the professional metamorphosis nursing students as a grounded theory was introduced. The theory was compared with related models and theories in the nursing literature. The applications and practical suggestions were provided in the nursing education. Conclusions This study introduced "professional metamorphosis of nursing students" as a grounded theory in the sociocultural context of the health system of Iran. The nursing students’ experiences during these stages (dependence, disintegration, and integration) and surrounding professional and extra- professional contexts help the nurse educators and administrators to develop effective educational interventions. Keywords: Socialization; Professionalization; Metamorphosis; Nursing Education; Iran